(untitled) - Spilsbury, Louise (Oxford, 2010)
This exciting new series of non-fiction readers provides interesting and educational content, with activities and project work. The readers are graded at four levels, from 3 to 6, suitable for students from age 8 and older
Keywords: Nguồn năng lượng,English language,Power resources,Tiếng Anh; Văn học thiếu niên,Reading comprehension,Juvenile literature,Đọc hiểu